2019
DOI: 10.4274/tjps.88709
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Roselle Aqueous Extracts-HPMC 6000 Gel on the Growth of Staphylococcus aureus ATCC 25923

Abstract: INTRODUCTION: Roselle (Hibiscus sabdariffa L.) is one of medicinal plants commonly used as beverage herbal medicine. Complexity compounds in the aqueous extracts have provided good antibacterial activity by which growth of Gram negative and positive bacteria are inhibited. The aims of this research were to formulate HPMC 6000 gel containing the extract and investigate inhibitory activity of the extract and its gel formula against Staphylococcus aureus ATCC 25923. METHODS: Thin-layer Chromatography on Silica-ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
(25 reference statements)
0
3
0
1
Order By: Relevance
“…The results showed that there was a zone of inhibition form extract at the concentrations of 10%; 5%; 2.5% and the MIC value of roselle extract was 2.5%. According to literature, to inhibit the bacterial growth of MRSA, roselle aqueous extract was used at a MIC 3% (Isnaeni et al, 2020) . Based on the classification of the zone of inhibition of bacterial growth, the MIC value of 2.5% which provides a 10 mm zone of inhibition is classified as potentially strong (Kowalska-Krochmal and Dudek-Wicher, 2021) .…”
Section: Antibacterial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that there was a zone of inhibition form extract at the concentrations of 10%; 5%; 2.5% and the MIC value of roselle extract was 2.5%. According to literature, to inhibit the bacterial growth of MRSA, roselle aqueous extract was used at a MIC 3% (Isnaeni et al, 2020) . Based on the classification of the zone of inhibition of bacterial growth, the MIC value of 2.5% which provides a 10 mm zone of inhibition is classified as potentially strong (Kowalska-Krochmal and Dudek-Wicher, 2021) .…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…The pharmacological activity of various parts of the rosela plant has been reported, one of which is roselle flower calyx as an antibacterial (Hassan et al, 2016) . Water extract of roselle flower calyx can inhibit the growth of S. aureus and K. pneumoniae bacteria with a minimum inhibitory concentration (MIC) value of 0.30 + 0.2 mg/mL (Isnaeni et al, 2020) and shows a 50% inhibitory concentration (IC 50 ) value of 178.62 + 3.63 𝜇g/mL (Jung et al, 2013) . Research conducted by Lee et al (2018) showed that the water extract of roselle calyx inhibited the growth of MRSA with MIC of 112-144 𝜇g/mL.…”
Section: Introductionmentioning
confidence: 99%
“…The Application of Film Chitosan-ZnO Nanoparticles-CTAB to S. aureus Three Petri dishes were used in this experiment. The procedure to prepare the inoculum suspension of S. aureus was adopted by Isnaeni et al (2020). The preparation of nutrient agar for used application of lm chitosan-ZnO nanoparticles-CTAB and ready to use are referred to procedure.…”
Section: 6mentioning
confidence: 99%
“…Kemudian plat silika dieluasi menggunakan fase gerak butanol : asam asetat : air (4:1:5). Setelah proses eluasi selesai plat silika dikeringkan di udara kemudian dilakukan uji kualitatif dengan penampak noda uap amonia (Isnaeni et al, 2020).…”
Section: Metodeunclassified